Negative consequence of benevolent sexism on efficacy and performance. Issue 3 (29th April 2014) - Jones, Kristen; Stewart, Kathy; King, Eden; Botsford Morgan, Whitney; Gilrane, Veronica; Hylton, Kimberly
Abstract : Purpose: – Previous research demonstrates the damaging effects of hostile sexism enacted towards women in the workplace. However, there is less research on the consequences of benevolent sexism: a subjectively positive form of discrimination. The paper aims to discuss these issues. Design/methodology/approach: – Drawing from ambivalent sexism theory, the authors first utilized an experimental methodology in which benevolent and hostile sexism were interpersonally enacted toward both male and female participants. Findings: – Results suggested that benevolent sexism negatively impacted participants' self-efficacy in mixed-sex interactions. Extending these findings, the results of a second field study clarify self-efficacy as a mediating mechanism in the relationship between benevolent sexism and workplace performance. Originality/value: – Finally, benevolent sexism contributed incremental prediction of performance above and beyond incivility, further illustrating the detrimental consequences of benevolently sexist attitudes towards women in the workplace.